(untitled) (Veterinary Science, 2017)
Four species from Baccharis genus (Compositae) are assessed due to antimicrobial activity against eight bacterial species. The modified Kirby Bauer method was used in the assay. The methalonic extracts from B. articulata, B. soliafolia, B. pingraea showed an inhibitory halo in comparison with Staphylococcus aureus, Streptococcus agalactiae, Staphylococcus epidermidis. None of the studied species showed activity against Gram negative bacteria. B. spartioides displayed no antimicrobial activity against none of the investigated bacterial species.